MANUFAKTUR BILAH HORIZONTAL AXIS WIND TURBINE MODEL TAPERLESS PADA MATERIAL KAYU - Deni Ade Purnomo (2021)
Wind Turbine is an energy conversion machine that converts kinetic energy into mechanical energy on its axis. In general, the workings of a Wind Turbine only utilize the thrust of the wind, so the greater the thrust, the greater the efficiency of the turbine. The purpose of this manufacturing process is to make blades from Wind Turbines that are suitable for wind speeds in the territory of Indonesia which can be made on a home scale with materials that are certainly strong, inexpensive, and easy to obtain. The manufacturing process carried out includes blade design, Airfoil selection, blade type selection, and material selection. The material used to make the blade is pine wood with an initial size of 120 cm x 15 cm x 4 cm. The manufacturing process is done by shaving the wood manually using a crab machine. The finishing process is done by sanding manually to form the appropriate blade. The result of the manufacturing is a Horizontal Axis Wind Turbine (HAWT) type with a total of 1 Taperless blade. The material used in the manufacture of this blade is pine wood and the type chosen in the manufacture of this blade uses the Airfoil USA-35B type.